It Takes Two to Talk about Prostate Cancer: A Qualitative Assessment of African-American Men’s and Women’s Cancer Communication Practices and Recommendations - Friedman, Daniela B. (2012)
Prostate cancer (PrCA) is the most commonly diagnosed non-skin cancer among men. African-American (AA) men in South Carolina have a PrCA death rate 150% higher than that of European-American (EA) men. This in-depth qualitative research explored AA men’s and women’s current practices, barriers, and recommended strategies for PrCA communication. A purposive sample of 43 AA men and 38 AA spouses/female relatives participated in focus groups (11 male groups; 11 female groups). A 19-item discussion guide was developed. Coding and analyses were driven by the data; recurrent themes within and across groups were examined. Findings revealed AA men and women agreed on key barriers to discussing PrCA; however, they had differing perspectives on which of these were most important. Findings indicate that including AA women in PrCA research and education is needed to address barriers preventing AA men from effectively communicating about PrCA risk and screening with family and healthcare providers.